2010
DOI: 10.1007/s00415-010-5584-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise induced oxidative stress on glutathione levels in Parkinson’s disease on and off medication

Abstract: Resting plasma glutathione (GSH) levels are lower in individuals with Parkinson's disease (PD) than any other neurological condition. Medications used to treat PD have also been shown to further decrease this depletion. Acute exercise has been shown to be an effective tool to produce oxidative stress in other populations as reflected in lowering levels of GSH. The purpose of this study was to determine how PD responds to acute exercise stress and how medication affects these responses. Fourteen men with PD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
(64 reference statements)
1
13
0
1
Order By: Relevance
“…It has been shown that the activation of brainderived neurotrophic factor and its receptor TrkB signaling pathway is involved in the neuroprotective effect of exercise against brain injury (Gerecke et al, 2012;Wu et al, 2011). On the other hand, reports demonstrate that long-term moderate exercise induces low level of reactive oxygen species (ROS), which may activate the endogenous antioxidant defense system (Elokda et al, 2010;Somani et al, 1995), though highintensity acute exercise increases oxidative stress and vulnerability to brain injury (Aguiar et al, 2010;Teixeira et al, 2009). The induction of adaptive antioxidant defense by regular exercise has therefore been suggested to be able to prevent oxidative stress-associated aging (Navarro et al, 2004) and neurodegeneration (Cechetti et al, 2012;Garcia-Mesa et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…It has been shown that the activation of brainderived neurotrophic factor and its receptor TrkB signaling pathway is involved in the neuroprotective effect of exercise against brain injury (Gerecke et al, 2012;Wu et al, 2011). On the other hand, reports demonstrate that long-term moderate exercise induces low level of reactive oxygen species (ROS), which may activate the endogenous antioxidant defense system (Elokda et al, 2010;Somani et al, 1995), though highintensity acute exercise increases oxidative stress and vulnerability to brain injury (Aguiar et al, 2010;Teixeira et al, 2009). The induction of adaptive antioxidant defense by regular exercise has therefore been suggested to be able to prevent oxidative stress-associated aging (Navarro et al, 2004) and neurodegeneration (Cechetti et al, 2012;Garcia-Mesa et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…The metabolism of dopamine (DA) itself creates a favorable environment for oxidative damage through intermediates such as DA-quinone and 3, 4-dihydroxy phenylacetaldehyde (Jackson and Smeyne , 2005). On the other hand reduced plasma levels of anti-oxidants such as glutathione and uric acid have been reported in PD patients (Elokda et al, 2010). …”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…The lower levels of glutathione were interpreted as a result of oxidative stress. 34 A study was conducted by Elokda et al, 35 to establish the effects of exercise induced oxidative stress on glutathione levels in Parkinson's disease during off and on medication. The study was conducted on the findings that show resting plasma GSH levels to be lower in people suffering from PD in comparison to other neurological conditions.…”
Section: Glutathione Deficit and Parkinson's Diseasementioning
confidence: 99%
“…Thus the findings showed that PD patients had lower levels of plasma GSH compared to healthy people at rest and peak exercise. 35 A study was conducted by Chen et al, 36 to establish whether increased oxidative damage in peripheral blood correlates with severity of PD. Basing their research on the findings that show neuronal dysfunction due to increased oxidative stress in PD patents, the researchers sought to investigate whether the pathological changes that occur in the brain of PD patients are also present in peripheral tissues.…”
Section: Glutathione Deficit and Parkinson's Diseasementioning
confidence: 99%